IMF Staff papers : Volume 8 No. 1. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1960)
This paper focuses on the IMF policies and procedures in relation to the compensatory financing of commodity fluctuations. The paper discusses the nature of the fluctuations affecting the balance of payments of primary exporting countries, the IMF's policies and practices in relation to the financing of such fluctuations. Throughout the study, the term 'compensatory financing' is used in a broad sense to include movements in a country's own official reserves as well as any international borrowing or any other international. While the IMF has shown its readiness to assist its members in meeting short-term payments difficulties arising from external causes, including commodity fluctuations, it cannot be said that the greater part of its transactions with primary producing countries have been of this character. The volume of new transactions with such countries has been as high in years of high commodity prices and high export proceeds as in years of low prices and low proceeds. The IMF resources have recently been enlarged by means of a general increase in quotas.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet